2015
DOI: 10.1055/s-0035-1552585
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Paradigms in Diminished Ovarian Reserve and Advanced Reproductive Age in Assisted Reproduction: Customization Instead of Conformity

Abstract: As women are increasingly delaying childbearing into their 30s and beyond, diminished ovarian reserve (DOR) and advanced reproductive age (ARA) patients are bound to become a large proportion of all assisted reproductive technology practices. Traditional controlled ovarian stimulation (COS) protocols for DOR and/or ARA have had some limited success, but pregnancy rates are lower and cycle cancellation rates are higher than their younger counterparts with normal ovarian reserve. Though many physicians have a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…In these situations, there are usually no oocytes retrieved despite apparently normally growing ovarian follicles with adequate estradiol (E2) concentrations using meticulous repeated follicular aspiration and flushing (Kumaran et al 2015). Patients with poor prognosis also tend to have high cancellation rates, along with lower pregnancy and live birth rates (Reed et al 2015). Thus, more research has gone into the mechanisms of follicular growth and how clinicians can better manipulate the natural female cycle in order to yield better results for women with poorer response to treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In these situations, there are usually no oocytes retrieved despite apparently normally growing ovarian follicles with adequate estradiol (E2) concentrations using meticulous repeated follicular aspiration and flushing (Kumaran et al 2015). Patients with poor prognosis also tend to have high cancellation rates, along with lower pregnancy and live birth rates (Reed et al 2015). Thus, more research has gone into the mechanisms of follicular growth and how clinicians can better manipulate the natural female cycle in order to yield better results for women with poorer response to treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, estrogen priming was performed to allow for follicular synchronization prior to the stimulation. For minimal stimulation IVF ( Figure 1 ), clomiphene citrate 100mg was given orally for 10 days starting on menstrual cycle day 2-3 ( Reed et al ., 2015 ).One hundred fifty international units (IU) of human menopausal gonadotropin (HMG) were added for days 5, 7, and 9. For mild stimulation, patients were on recombinant FSH 150 IU daily.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the lower dose of gonadotropin used may allow for better quality oocytes and embryos ( Baart et al ., 2007 ; Haas et al ., 2015 ). We offer the minimal stimulation approach to patients with expected poor ovarian response mainly due to diminished ovarian reserve and/or advanced reproductive age with a plan for embryo accumulation and subsequent frozen embryo transfer (FET) ( Reed et al ., 2015 ). A commonly prescribed minimal ovarian stimulation protocol uses daily clomiphene citrate (CC) and a small amount of gonadotropin on days 5, 7, and 9 of the ovarian stimulation ( Figure 1 ) ( Reed et al ., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is reported that in vitro fertilization and embryo transfer (IVF-ET) could improve the pregnancy rate of husband and wife with infertility; however, the pregnancy rate is still less than 50% [3,4]. The reasons for infertility are complex, and the diminished ovarian reserve (DOR) is one of the most important reasons [5,6]. Ovarian reserve (OR) is defined as the number and quality of remaining oocytes in ovarian cortex, reflects the fertility potency and reproductive endocrine function of women [7,8].…”
Section: Introductionmentioning
confidence: 99%